2022
DOI: 10.1021/acsapm.2c00335
|View full text |Cite
|
Sign up to set email alerts
|

Cardanol-Derived Epoxy Resins as Biobased Gel Polymer Electrolytes for Potassium-Ion Conduction

Abstract: In this study, biobased gel polymer electrolyte (GPE) membranes were developed via the esterification reaction of a cardanol-based epoxy resin with glutaric anhydride, succinic anhydride, and hexahydro-4-methylphthalic anhydride. Nonisothermal differential scanning calorimetry was used to assess the optimal curing time and temperature of the formulations, evidencing a process activation energy of ∼65–70 kJ mol –1 . A rubbery plateau modulus of 0.65–0.78 MPa and a crosslinking density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…5 Recently, various types of post-Li batteries with new cations such as Na, K, and Mg have been investigated owing to their low cost and high energy density. [6][7][8][9][10][11] Among the post-Li batteries, Na-ion batteries have attracted increasing attention because of the abundance of Na. 12,13 Na ASSBs have been investigated for large-scale applications, such as ESS, which require high safety.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, various types of post-Li batteries with new cations such as Na, K, and Mg have been investigated owing to their low cost and high energy density. [6][7][8][9][10][11] Among the post-Li batteries, Na-ion batteries have attracted increasing attention because of the abundance of Na. 12,13 Na ASSBs have been investigated for large-scale applications, such as ESS, which require high safety.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, sustainable gel-polymer/solid-state electrolytes are being developed to overcome the hurdles of safety, stability, and dendrite growth. [25][26][27][28] Recently, Bella and co-workers designed lignin-based membranes by crosslinking of a preoxidized Kraft lignin matrix with an ethoxylated difunctional oligomer. Those gel polymer electrolytes (GPEs) exhibited decent conductivity of 10 À 3 S cm À 1 and > 4 V stability window with K + .…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable materials have also reached momentum for the fabrication of the next generation of batteries. For instance, sustainable gel‐polymer/solid‐state electrolytes are being developed to overcome the hurdles of safety, stability, and dendrite growth [25–28] . Recently, Bella and co‐workers designed lignin‐based membranes by crosslinking of a pre‐oxidized Kraft lignin matrix with an ethoxylated difunctional oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that K + can passivate defects and optimize interfaces to improve power conversion efficiency (PCE). [31][32][33] For example, Luo et al doped potassium cinnamate (PC) into a perovskite precursor solution. This strategy enhances the quality of the film, passivates defects and advances the photoluminescence intensity.…”
Section: Introductionmentioning
confidence: 99%